أثر سمات الشخصية متغيرا وسيطا في العلاقة بين أساليب المعاملة الوالدية والصحة النفسية لدى طلبة جامعة المرقب في ليبيا - سعد، نجاة محمد (Kulliyah of Education, International Islamic University Malaysia, 2021)
The present study aims to verify the intermediate effect of personality traits in the relationship between parents and father's mental health methods among the students of the bachelor's degree at Al-Marqab University in Libya. To achieve this goal, three measures were applied for both parental treatment methods, personality traits and mental health, (383) of the students of the bachelor's degree at the University of Al-Muraqeb in Libya for the academic year 2018/2019. All the students of the university included their scientific and disciplinary level. The researcher used the SPSS program in the preliminary analysis stage, And the descriptive analysis of the demographic information of the study sample. SmartPLS 3 was used in the analysis of the standard study model. The results showed that it is characterized by evidence of validity and realability. It was then used in the analysis of the structural study model. (Father), personality traits and mental health among the students of Al-Muraqqab University in Libya, as well as a direct positive relationship between the personality traits and the students' mental healh, regarding the intermediate role of personality traits in the relationship between parental treatment methods Mental health The results of the study also showed a mediating effect in this relationship, and accordingly the researcher recommended conducting a similar study that the sample of the Libyan school students.